(untitled) (Research, Society and Development, 2021)
The fish processing industry generates a large amount of waste, that can be a nutrients source to the foods enrichment, such as cake that has low proteins, and consumed for different social classes. This study aimed to produced cakes with Nile tilapia (Orechromis niloticus) waste flour (NWF), formed by head, fins and the spine with meat remaining from filleting process, and evaluate its chemical and sensory properties. The formulations cakes with NWF obtained products with higher protein contents, essential fatty acids, and minerals, especially calcium and phosphorus, and lower car-bohydrates contents in relation to Control formulation (without NWF). The cakes with NWF had sensory acceptance (scores higher than 7.0 from 9.0 points) and purchase intention (scores higher than 3.8 from 5.0 points) and did not differ from the Control. The cakes with NWF can be a way to increase the supply of essential nutrients to the population through a popular and sensorial accepted product. This study showed that Nile tilapia waste flour (NWF) heads stands out a promising source for producing cake with high nutritional quality, positive economic potential, better physicochemical properties and, food industry solid waste reduction by used in food.